PENGEMBANGAN FLIPBOOK INTERAKTIF BERBASIS ADDIE UNTUK PEMBELAJARAN PUISI DI SMA - Al Ashadi Alimin; Hariyadi; Siget, Gabriel Yucu (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to address low learning motivation and the lack of variety in teaching resources for poetry material at SMA Negeri 1 Sandai through the development of flipbook-based learning media. This study used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects included six expert validators, one Indonesian language teacher, and 28 grade XI students as product users. Data collection was conducted using interviews and questionnaires, then analyzed descriptively and quantitatively. The results showed that the developed flipbook product obtained a validity score of 93.66% (very valid) and a practicality score of 93.79% (very practical). Furthermore, the product effectiveness test validated a significant increase in students' cognitive learning outcomes with an average Normalized Gain (N-Gain) score of 0.62 (moderate category). These empirical findings indicate that the integration of audio-visual elements in flipbooks is effective in visualizing abstract poetry concepts into concrete ones and maintaining student learning motivation. The implications of this study recommend the use of interactive media as an alternative solution for literature learning in the digital era.